2016
DOI: 10.1016/j.cmet.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A Ribosomal Perspective on Proteostasis and Aging

Abstract: As the first and most direct process influencing the proteostasis capacity of a cell, regulation of translation influences lifespan across taxa. Here we highlight some of the newly discovered means by which translational regulation affects cellular proteostasis, with a focus on mechanisms that may ultimately impinge upon the aging process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 95 publications
10
82
0
1
Order By: Relevance
“…Reprogramming, currently an experimental tool to study development and cellular differentiation, may provide additional insights into the mechanisms of aging. Proposed drivers of physiological aging include the accumulation of DNA damage, increased ROS production, telomere shortening, cellular senescence, and defects in nuclear envelope architecture (Bernardes de Jesus and Blasco, 2013; Guarente, 2008; Haigis and Sinclair, 2009; Kennedy and Lamming, 2016; Soultoukis and Partridge, 2016; Steffen and Dillin, 2016). Multiple studies using animal models have demonstrated that the manipulation of these aging drivers leads to the manifestation of molecular hallmarks of aging that are shared between premature aging models and physiological aging (García-Prat et al, 2016; Mitchell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming, currently an experimental tool to study development and cellular differentiation, may provide additional insights into the mechanisms of aging. Proposed drivers of physiological aging include the accumulation of DNA damage, increased ROS production, telomere shortening, cellular senescence, and defects in nuclear envelope architecture (Bernardes de Jesus and Blasco, 2013; Guarente, 2008; Haigis and Sinclair, 2009; Kennedy and Lamming, 2016; Soultoukis and Partridge, 2016; Steffen and Dillin, 2016). Multiple studies using animal models have demonstrated that the manipulation of these aging drivers leads to the manifestation of molecular hallmarks of aging that are shared between premature aging models and physiological aging (García-Prat et al, 2016; Mitchell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic inhibition of tRNA synthetases, which may decrease mRNA translation, extends C. elegans lifespan2829. daf-2 mutants display reduced translation rates30, and reduced translation confers longevity in multiple organisms31. Thus, increased NMD activity by reduced IIS may prevent age-dependent increases in abnormal transcripts, including tRNA synthetase genes, and this may in turn contribute to the longevity of daf-2 mutants by decreasing translation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the critical role of proteins in regulating a large variety of biological processes, protein synthesis, folding and subsequent degradation (i.e. protein homeostasis or “proteostasis”) are fundamental to maintain optimal cellular function and tissue homeostasis during normal conditions and in response to environmental stress [56, 57]. This is of particular importance to the lung, which due to its anatomical structure is in direct contact with the outside world and continuously challenged by inhaled insults including cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%